Modelling bookmaking odds for the English Premier League. - Tan, Aurelius Kok Keong. (2008)
Assuming that goals scored are independent poisson random variables, a poisson regression model estimating the means of these random variables is formulated. Data from 1140 English Premier League football matches fitted into the model. The motivation of this paper is to derive efficient soccer bookmaking odds from the results.